PERLINDUNGAN HUKUM BAGI KREDITOR ATAS ADANYA KEPAILITAN (STUDI PUTUSAN NO. 31/PDT.SUS-PAILIT/2023/PN NIAGA JKT. PST.) - DARI, WULAN; M.Sudirman (Universitas Tangerang Raya, 2024)
Bankruptcy is a way out to solve the debt problem that presses a debtor, where the debtor does not have the ability or good faith to pay these debts to his creditors and the rights of creditors can still be protected. This study aims to explain the legal efforts made by creditors so that their legal interests are protected and a form of legal protection for creditors due to the debtor's being declared bankrupt in the study of Decision Number No. 31/Pdt.Sus-Pailit/2023/PN Niaga Jkt. Pst.. This research uses normative juridical research and library research by conducting an assessment of the Laws and Regulations and books related to the title of this thesis. The results showed that the Decision of the Commercial Court decided the bankruptcy of PT. Multi Inti Karya. The legality of filing for bankruptcy by PT. Citra Harda Mandiri which is based on part of the receivables from PT.Multi Inti Karya which have met the elements of bankruptcy, namely Article 2 paragraph (1) UUK-PKPU because it is known that the legality made by PT. Multi Inti Karya. with another party, namely Cv. Dwi Sinergy Engineering on the implementation of the agreement, transferred a number of its receivables, so that the bankruptcy status received by PT. Multi Inti Karya caused the loss of its rights in the field of assets.